Contribuição e distribuição de recursos : uma análise comportamental do Jogo dos Bens Públicos - Ferreira, André Luíz (Universidade Federal de São Carlos, 2017)
Corruption is an object of study in several researches, but only recently it began to be investigated experimentally. Despite the progress, some gaps remain open, particularly in regards to the variables of which the observed behaviors are function, one aspect in which behavior analysis can contribute to operationalize the phenomenon and investigate the environmental variables that control these behaviors characterized as corrupt. One way to study this phenomenon is to expose the participants to a context in which they need to contribute to producing a particular public good, and then need to make decisions about how this good will be distributed among all participants. In this context, the participant can make three decisions: distribute in an egalitarian way; Distribute in an unequal way, favoring others, or distribute in an unequal way, favoring their own gains. A participant who makes distributions unequally for his own benefit shall behaving in a manner analogous to that described in the crime of embezzlement. Through the Public Goods Game (JBP), by modifying its original protocol, allowing the participants to manage the public resource, deciding how it will be distributed, it is possible to experimentally study this type of corrupt behavior. The aim was to investigate how the participants managed public resources under a PGG. Six participants were exposed to the procedure. They had to decide how the resource produced by her/his own contribution and that of the other players would be distributed among them. Five participants made unequal distributions, i.e, allocated most of the resources to themselves. This type of distribution is in correspondence with an embezzlement definition, allowing an approximation to real contexts. From these results, we suggest changes in the contingencies that control the occurrence of this type of behavior.
Keywords: Análise do comportamento; Tomada de decisão; Teoria dos jogos; Jogo dos bens públicos; Corrupção; Behavior analysis; Decision making; Game theory; Public goods game; Corruption; CIENCIAS HUMANAS::PSICOLOGIA